Steatohepatitis and fibrosis in chronic Hepatitis C patients: is there any association? - Hasmoni, Mohamed Hadzri; Salleh, Rosemi; Jaafar, Khairul Azhar; Jaafar, Mohd. Hanizam; Abas, Ariff (Springer, 2011)
Background: Hepatic steatosis and disturbances in lipid metabolism has been identified as one of the metabolic disorders in hepatitis C (HCV) infection. This study was to examine the possible association of steatohepatitis with the degree of fibrosis in chronic HCV patients.